Obstacle avoidance training in virtual environments leads to limb-specific locomotor adaptations but not to interlimb transfer in healthy young adults. (7th May 2021) - Weber, A.; Friemert, D.; Hartmann, U.; Epro, G.; Seeley, J.; Werth, J.; Nickel, P.; Karamanidis, K.
Abstract: Obstacle avoidance is one of the skills required in coping with challenging situations encountered during walking. This study examined adaptation in gait stability and its interlimb transfer in a virtual obstacle avoidance task. Twelve young adults walked on a treadmill while wearing a virtual reality headset with their body state represented in the virtual environment. At random times, but always at foot touchdown, 50 virtual obstacles of constant size appeared 0.8 m in front of the participant requiring a step over with the right leg. Early, mid and late adaptation phases were investigated by pooling data from trials 1–3, 24–26 and 48–50. One left-leg obstacle appearing after 50 right-leg trials was used to investigate interlimb transfer. Toe clearance and the anteroposterior margin of stability (MoS) at foot touchdown were calculated for the stepping leg. Toe clearance decreased over repeated practice between early and late phases from 0.13 ± 0.05 m to 0.09 ± 0.04 m (mean ± SD, p < 0.05). MoS increased from 0.05 ± 0.02 m to 0.08 ± 0.02 m ( p < 0.05) between early and late phases, with no significant differences between mid and late phases. No differences were found in toe clearance and MoS between the practiced right leg for early phase and the single trial of the left leg. Obstacle avoidance during walking in a virtual environment stimulated adaptive gait improvements that were related in a nonlinear manner to practice dose, though such gait adaptations seemed to be limited in their transferability between limbs.